First Generation Solar Cell: History And Development Of Silicon-Based Photovoltaics - Gultom, Noto Susanto; Sugandi, Adinda A. Nur; P. Dewi, Aisyah; Qulsum, Kirana; Elisabet, Mona; Aprillia, Bandiyah Sri; Hidayat, Sahrul; Nilam, Putri Nuri; Simanjuntak, Mayer (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2025)
The  global  transition  toward  new  and  renewable  energy  sources  to  address environmental issues and the limitations of conventional energy reserves remains a priority. Solar energy,  through  photovoltaic  technology,  emerges  as  a  promising  option  for  mitigating  the environmental  impact  of  traditional  energy.  The  fact  that  solar  energy  is  a  sustainable  resource and a viable means to reduce reliance on fossil fuels supports this. Solar cells are  devices made from  semiconductor  materials  capable  of  converting  solar  energy  into  electrical  energy.  We categorize first-generation solar cells into silicon monocrystalline, silicon polycrystalline, and III- V  single  junctions  based  on  GaAs.  This  article  reviews  the  characteristics  of  first-generation silicon-based  solar  panels,  including  efficiency,  light  absorption,  and  transmission,  which dominate the global market. This review aims to provide an in-depth understanding of the factors influencing the performance of silicon-based solar cells, which will contribute to the development and application of solar cell technology in the future. Keywords: solar energy, solar cell, silicon, monocrystalline, polycrystalline